Adverse events of PD-(L)1 inhibitors plus anti-VEGF(R) agents compared with PD-(L)1 inhibitors alone for cancer patients: a systematic review and meta-analysis - Tang, Qiyu; Wu, Dawei; Huang, Huiyao; Fang, Hong; Wu, Ying; Liu, Funan; Li, Ning (Frontiers in Pharmacology, 2023)
Background: Anti-PD-(L)1 antibody monotherapy or in combination with VEGF(R) blockade has been applied widely for cancer treatment. Whether combination therapy increases irAEs still remains controversial. Methods: A systematic review and meta-analysis comparing PD-(L)1 and VEGF(R) blockade combination therapy with PD-(L)1 inhibitors alone was performed. Phase II or III randomized clinical trials reporting irAEs or trAEs were included. The protocol was registered with PROSPERO, CRD42021287603. Results: Overall, 77 articles were included in the meta-analysis. A total of 31 studies involving 8,638 participants were pooled and an incidence for PD-(L)1 inhibitor monotherapy with any grade and grade ≥3 irAEs of 0.25 (0.20, 0.32) and 0.06 (0.05, 0.07), respectively, were reported. Two studies with 863 participants pooled for PD-(L)1 and VEGF(R) blockade showed that an incidence of any grade and grade ≥3 irAEs were 0.47 (0.30, 0.65) and 0.11 (0.08, 0.16), respectively. Regarding pairwise comparisons for irAEs, only one study was included, indicating no significant difference between the two regimens in terms of colitis, hyperthyroidism, and hypothyroidism for any grade and grade ≥3, while there was a trend of higher incidence for any grade hyperthyroidism under the combination therapy. The incidence of reactive cutaneous capillary endothelial proliferation (RCCEP) was as high as 0.80 under camrelizumab monotherapy. Conclusion: Total incidences of any grade and grade ≥3 irAEs were higher in the combination treatment group. Direct comparisons indicated no significant difference between the two regimens for any grade and grade ≥3 specific irAEs. RCCEP and thyroid disorders need to be paid attention to clinically. Moreover, trials with direct comparisons are needed and the safety profiles of the two regimens should be further explored. Exploration of the mechanism of action and regulatory management of adverse events should be enhanced. Systematic Review Registration: https://www.crd.york.ac.uk/prospero/display_record.php?RecordID=287603, identifier CRD42021287603